1993
DOI: 10.1038/hdy.1993.163
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of inbreeding and outbreeding in hermaphroditic Arianta arbustorum (L.) (land snail)

Abstract: Inbreeding depression was studied in the outcrossing hermaphroditic land snail Arianta arbustorum, by comparing the reproductive performance of full-sib pairs (inbreeding) and pairs of unrelated individuals (outbreeding). Fecundity (number of eggs laid) was not found to differ significantly between inbreeding and outbreeding pairs under laboratory conditions, but fertility (the proportion of eggs that hatched) and the number of hatchlings produced by inbreeding pairs were significantly lower than those of outb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
59
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(60 citation statements)
references
References 20 publications
(23 reference statements)
0
59
1
Order By: Relevance
“…The estimated number of lethal equivalents in the Mandarte song sparrows is similar to those reported for Japanese quail but above what was reported for other laboratory populations and below many of those reported for zoo populations. Hence, although some studies have reported more pronounced inbreeding depression in a natural environment than in the laboratory (e.g., Chen 1993;Jimenez et al 1994), the comparison of the estimates of genetic load of zoo and wild populations indicates that other factors also influence the degree of inbreeding depression. In particular, lower selection pressures might lead to the maintenance of higher frequencies of deleterious alleles in zoos.…”
Section: Lethal Equivalentsmentioning
confidence: 99%
“…The estimated number of lethal equivalents in the Mandarte song sparrows is similar to those reported for Japanese quail but above what was reported for other laboratory populations and below many of those reported for zoo populations. Hence, although some studies have reported more pronounced inbreeding depression in a natural environment than in the laboratory (e.g., Chen 1993;Jimenez et al 1994), the comparison of the estimates of genetic load of zoo and wild populations indicates that other factors also influence the degree of inbreeding depression. In particular, lower selection pressures might lead to the maintenance of higher frequencies of deleterious alleles in zoos.…”
Section: Lethal Equivalentsmentioning
confidence: 99%
“…Although some snails, such as Rumina decollata (Subulinidae) (Selander & Kaufman 1973) or Liguus fasciatus (Bulimulidae) (Hillis 1989) undergo extensive self-fertilization, this would not appear to be true of the helicids, which are e¡ectively obligate outbreeders. Chen (1993) found that Arianta arbustorum was able to self but con¢rmed that it normally does not do so. He reported a marked loss of ¢tness in sib matings compared with matings between unrelated individuals, and concluded that cross-fertilization is maintained by strong inbreeding depression.…”
Section: (A) Heterosismentioning
confidence: 99%
“…A number of recent studies have suggested that the deleterious consequences of inbreeding are reinforced under harsh environmental conditions Reed et al 2003Reed et al , 2007Da Silva et al 2006), and that studies investigating inbreeding effects under laboratory conditions that are often benign may not be representative for consequences of inbreeding in variable natural environments (Chen 1993;Pray et al 1994;Kristensen et al 2008a). On the other hand, studies of the effects of inbreeding and interactions between inbreeding and the environment in natural populations often suffer from low replication, incomplete pedigree information, lack of proper controls and the fact that the presumed neutral molecular markers often used may not reflect levels of detrimental and adaptive genetic variation.…”
Section: Introductionmentioning
confidence: 99%